If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10+2z=10-8z
We move all terms to the left:
-10+2z-(10-8z)=0
We add all the numbers together, and all the variables
2z-(-8z+10)-10=0
We get rid of parentheses
2z+8z-10-10=0
We add all the numbers together, and all the variables
10z-20=0
We move all terms containing z to the left, all other terms to the right
10z=20
z=20/10
z=2
| 7=w+2.5. | | -6(2x-9)+6x=-7 | | (-20-10y)+y=-2 | | -10+2z=10−8z | | 4(2h+3)=2(5h-2)+6;h | | –10+2z=10−8z | | 5(x-2)=4(2x+5);x | | 5(x−2)=4(2x+5);x | | 7y+5=3y+17;y | | 7+5(x-2)=5-9(x-5) | | 6-3a=21= | | x+2x=1-16;x |